The Politics of Curriculum Implementation in Africa. - Ssempala, Fredrick; Namazzi, Winnifred Birabwa (Kabale University, 2024)
The curriculum decisions made about teaching are not just about educational content, not about whose voices are heard, or whose knowledge is valued, but also how societies envision education. So, understanding the dynamics of curriculum politics is fundamental to understanding the nature of implementation and the success possibilities of any curriculum implementation. This paper therefore found it important to investigate the kind of curriculum politics that prevails in Africa and how it influences curriculum development in schools. The objectives of the study were to explore how politics influences the curriculum implementation process in Africa and establish strategies that can improve the curriculum implementation process amidst the political dynamics. The study adopted an approach of methodological inquiry based on secondary data sources. Findings revealed the politicization of curricula in Africa significantly impacts teacher autonomy, teaching methodologies, and opportunities for professional development along the way through restrictive guidelines, standardized testing pressures, and conflicting pedagogical approaches. The study recommends addressing the politics of implementation through a multifaceted approach, where emphasis on prioritizing transparency, teacher empowerment, flexibility, and ethical inclusivity, can be used to navigate the challenges and create an educational ecosystem that empowers individual educators.